Technology, knowledge and beluga whales in Ulukhaktok, NT, Canada. Issue 4 (April 2019) - Collings, Peter
Abstract : This paper examines knowledge about beluga whales in Ulukhaktok, Canada. During summer 2014, hunters in Ulukhaktok landed 33 beluga whales. The hunt was unprecedented: beluga whales are only rarely encountered in local waters, and there is no tradition among Ulukhaktomiut for hunting beluga. Observations of the 2014 hunt and interviews subsequently conducted during 2015 suggest that, although Ulukhaktomiut claimed to lack facts about beluga whales, processual knowledge about beluga whales emerges materially in the application of the cell phone as a mechanism for organising hunts, in the experimentation with lances as killing implements, and through the development of practices for distributing meat and maktaq following a successful hunt. These processes, both material and social, highlight the complexities of constructing knowledge about a novel species while producing and negotiating community-building.